Improving Gross Motor Skills in Early Childhood Through Throwing and Catching Games Catch Football in Group B RA Darussalam NW Pungkang Academic Year 2024/2025 - Rukyah, Rukyah; Aini, Baiq Halimatuz Zuhrotul; Ismayadi, Ismayadi (JUPE : Jurnal Pendidikan Mandala, 2025)
This study is entitled Improving Gross Motor Skills of Early Childhood Through Throwing and Catching Ball Games in Group B RA Darsussalam NW Pungkangng in the 2024/2025 Academic Year. This study aims to develop gross motor skills of children aged 5-6 years through throwing and catching ball games in group B RA Darsussalam NW Pungkangng. Formulate the research problem as follows: "Can throwing and catching the ball develop children's gross motor skills in Group B RA Darsussalam NW Pungkang in the 2024/2025 Academic Year. This study uses the Classroom Action Research (CAR) model, with two cycles, where each cycle consists of four stages, namely: planning, implementation, observation, and reflection. The research subjects were 16 children consisting of 8 boys and 8 girls in group B aged 5-6 years. The methods used were: observation, interviews, and documentation, the results of children's abilities through games. The results of this study quantitatively are in the aspect of balance 54.16% in cycle 1, meeting 1, increased by 62.5% in meeting 2. The aspect of strength in cycle 1, meeting 1 0.5208% increased by 0.5625% in meeting 2. The aspect of flexibility in cycle 1, meeting 1 0.5208% increased at meeting 2, namely 0.625%. While in cycle 2 meeting 1 79.16% experienced a decrease in the 2nd meeting 0.7916%. The strength aspect at meeting 1 cycle 2, namely 68.75%, experienced an increase in the 2nd meeting, namely 75.00%. The flexibility aspect at meeting 1 cycle 2 had a value of 70.83% and experienced an increase of 79.16% at the 2nd meeting.